150SAFETY AND EFFECTIVENESS OF TRANSAORTIC APPROACH FOR TRANSCATHETER AORTIC VALVE IMPLANTATION: PROCEDURAL AND MID-TERM OUTCOMES OF 232 CONSECUTIVE PATIENTS AT A SINGLE CENTRE. (October 2014) - DaPrati, A.; Romano, M.; Tizzano, F.; Le Houérou, D.; Farge, A.; Lefèvre, T.; Chevalier, B.; Morice, M.C.
Abstract : Objectives: Transcatheter aortic valve implantation with transaortic approach (TAo-TAVI) has been recently proposed for patients with unsuitable peripheral vascular access, significant respiratory disease and poor left ventricular function. We studied the efficacy and safety of TAo-TAVI with the Edwards Sapien XT and the Medtronic CoreValve devices. Methods: Out of 901 patients receiving TAVI since 2006, 232 consecutive patients underwent TAo-TAVI between January 2011 and March 2014. Aortic root condition, valve anatomy and annulus size were carefully assessed by multislice computed tomography (MSCT). The aorta was exposed through an inverted "T" manubriotomy. Procedural and mid-term results were evaluated according to the VARC2 criteria. Results: Mean age was 84 ± 5 years and logistic EuroSCORE 15 ± 11.1%. The Sapien XT was used in 69.4% and the CoreValve in 30.6% of patients. Full sternotomy allowed concomitant off-pump coronary artery grafting (OPCAB) (1–5 grafts) in 33 patients (14.2%) with coronary artery disease (CAD) unsuitable for percutaneous coronary intervention (PCI). Device success rate was 95%. Mean fluoroscopy time was 13.3 ± 7.6 min and contrast medium administration 113.5 ± 48.8 ml. Postprocedural paravalvular leakage (PVL) ≥2/4 was observed in 7.3%. Open chest surgery was required in 3.9% [3 aortic dissections, 3 valve embolisations, 2 left main coronary artery (LMCA) occlusions, 1 annulus rupture]. Cerebrovascular accidents (CVA) occurred in 1.3%. Transfusion ≥4 units was required in 11.6%. AKI grade 3 occurred in 1.7%. New pacemakers were implanted in 9.9%. ICU and total hospital stay were 6 ± 5 and 15 ± 10 days, respectively. Thirty-day mortality was 7.4%. Mean follow-up duration was 18 ± 6 months. Mortality at follow-up was 18.1%. NHYA class I and II included 88% of the survivors without prosthetic dysfunction at echo (mean gradient 10.5 ± 5.9). Conclusion: The transaortic approach confirms its safety and effectiveness with satisfactory procedural and mid-term outcomes with both the currently available devices.